2012
DOI: 10.1111/j.1582-4934.2011.01383.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells show radioresistance in vivo

Abstract: Irradiation impacts on the viability and differentiation capacity of tissue-borne mesenchymal stem cells (MSC), which play a pivotal role in bone regeneration. As a consequence of radiotherapy, bones may develop osteoradionecrosis. When irradiating human bone-derived MSC in vitro with increasing doses, the cells’ self-renewal capabilities were greatly reduced. Mitotically stalled cells were still capable of differentiating into osteoblasts and pre-adipocytes. As a large animal model comparable to the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…These findings signify the higher alertness and readiness of the DNA damage response machinery after RT exposure. These same mechanisms have been reported to be responsible for bmMSCs RT resistance [71,95,104,106,184,190].…”
Section: Chapter 7 Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These findings signify the higher alertness and readiness of the DNA damage response machinery after RT exposure. These same mechanisms have been reported to be responsible for bmMSCs RT resistance [71,95,104,106,184,190].…”
Section: Chapter 7 Discussionmentioning
confidence: 85%
“…These mechanisms includes: rapid formation of -H2AX for robust DSBs repair activation, time efficient G2/M arrest activation, competent DSBs repair, low IR-induced apoptotic response, stimulated expression of DNA damage repair-related genes, significantly high expression of the major player proteins in different IR-induced DNA damage repair pathways including HRR, NHEJR and other pathways; namely, DNAPKcs, RAD-51 p-ATM, CHEK2 and others, and activated the anti-oxidant machinery [91,95,96,184,189]. Even more, one study suggested such radioresistance of bone marrow-derived MSCs in-vivo [190]. Until now, to our knowledge, no studies have investigated the radiosensitivity/resistance of MSCs from adipose tissue origin.…”
Section: 54d)mentioning
confidence: 99%
“…Single-cell suspension was obtained by passing through an 18-gauge needle and filtered with a nylon membrane, followed by erythrolysis in buffered 0.14-M NH 4 Cl. Cells were cultured in L-glutamine Dulbecco's minimum essential medium (LDMEM; Gibco®, Life Technologies Ltd, Grand Island, NY) containing 15% foetal bovine serum (FBS; Gibco) in a humidified atmosphere of 5% CO 2 at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…3 Since HSPCs are more sensitive to radiation, mesenchymal stem cells (MSCs) luckily have an intrinsic radiation-resistant phenotype. 4,5 Although effective radiation countermeasure approaches were initiated six decades ago, very few have unanimous endorsement by health professionals. Radiation protectors [such as WR-2721, Toll-like receptor ligands, flavonoids, Ex-RAD® (Onconova Therapeutics Inc., Newton, PA) and vitamin E] are prophylactic agents that are administered before exposure to prevent radiation-induced cellular and molecular damage.…”
mentioning
confidence: 99%
“…Cell endurance to irradiation is affected by the ability to produce antioxidants and the ability to repair DNA damage. 22 There are two mechanisms of DNA repair: non-homologous end joining (NHEJ) and homologous recombination (HR). The NHEJ has six components: Ku70, Ku80, DNA-PK, XRCC4, DNA ligase IV (LigIV), and XRCC4-like factor (XLF).…”
Section: Resultsmentioning
confidence: 99%